2020
DOI: 10.3390/v12091050
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insights into the Sewage RNA Virosphere of a Large City

Abstract: Sewage-associated viruses can cause several human and animal diseases, such as gastroenteritis, hepatitis, and respiratory infections. Therefore, their detection in wastewater can reflect current infections within the source population. To date, no viral study has been performed using the sewage of any large South American city. In this study, we used viral metagenomics to obtain a single sample snapshot of the RNA virosphere in the wastewater from Santiago de Chile, the seventh largest city in the Americas. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Since PBVs have been mostly detected in feces/gut contents of animals and humans with or without diarrhea, they were considered as opportunistic enteric pathogens of mammals (2,3). However, the identification of the prokaryotic RBS sequence upstream of putative ORF/s in PBV and PBV-like sequences indicate that PBVs might actually infect bacteria (7,8,13,21). Furthermore, by phylogenetic analysis of viral RdRp sequences, the partitivirus-picobirnavirus clade has been hypothesized to have originated in an as-yet-undiscovered lineage of prokaryotic RNA viruses (76).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since PBVs have been mostly detected in feces/gut contents of animals and humans with or without diarrhea, they were considered as opportunistic enteric pathogens of mammals (2,3). However, the identification of the prokaryotic RBS sequence upstream of putative ORF/s in PBV and PBV-like sequences indicate that PBVs might actually infect bacteria (7,8,13,21). Furthermore, by phylogenetic analysis of viral RdRp sequences, the partitivirus-picobirnavirus clade has been hypothesized to have originated in an as-yet-undiscovered lineage of prokaryotic RNA viruses (76).…”
Section: Discussionmentioning
confidence: 99%
“…Certain viruses that infect prokaryotes have been shown to be highly enriched for RBS sequences, such as the bacteriophages with segmented dsRNA genomes of family Cystoviridae (13,21,64,65). Similar to prokaryotic mRNAs and the cystoviruses, the RBS sequence, or its subset has been found to be conserved upstream of putative ORF/s (putative ORF1, 2 and 3 in gene segment-1 and putative ORF for RdRp in gene segment-2) in published PBV sequences from humans, animals and environmental samples (4,7,8,(11)(12)(13)(14)(15)(16)(17)(18)21). The presence of the conserved prokaryotic RBS sequence upstream of the putative start codon/s in representative PBV gene segment-1 sequences, gene segment-2 sequences of PBV GI and GII strains, and PBVlike RdRp sequences are shown in Table 1.…”
Section: Evidence That Picobirnaviruses Might Infect Prokaryotesmentioning
confidence: 99%
See 2 more Smart Citations
“…The oceans, which cover 71% of the Earth, are the most valuable resource for investigating the ecological and geographical diversity of viruses. However, to date, aquatic viromic studies tended to study phages but already showed enormous genetic diversity and ecological distributions (Roux, et al 2016; Vlok, et al 2019; Guajardo-Leiva, et al 2020; Gulino, et al 2020; Moon, et al 2020; Zhang, et al 2020). Although some studies included aquatic invertebrates (Magbanua, et al 2000; Thakur, et al 2002; Shi, et al 2016; Rosani, et al 2019), there is a lack of systematic study of these animals in a whole.…”
Section: Introductionmentioning
confidence: 99%